U-Dictionary Improves Pronunciation in Narrative Story Learning - Intan Meidy; Dian Rahma Santoso (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: English pronunciation is a fundamental component of oral communication competence, yet it remains one of the most challenging aspects for EFL learners, particularly in contexts where English phonology differs significantly from the native language. Specific Background: The integration of mobile-assisted language learning tools, such as the U-Dictionary application, offers audio models, phonetic transcription, and translation features that may support pronunciation practice during narrative story activities. Knowledge Gap: Previous research has largely emphasized vocabulary development or alternative media, leaving limited empirical evidence on the use of U-Dictionary for pronunciation within narrative text learning. Aims: This study examined whether the use of the U-Dictionary application significantly improves students’ English pronunciation when learning narrative stories. Results: Using a quantitative one-group pretest–posttest design with 24 ninth-grade students, the mean score increased from 50.00 to 58.13, and a paired sample t-test yielded a significance value of 0.047 (< 0.05), indicating a statistically significant difference after the intervention. Novelty: The study provides focused evidence on mobile dictionary–assisted pronunciation practice embedded in narrative story learning, particularly addressing difficulties with regular and irregular verb pronunciation. Implications: The findings suggest that accessible mobile applications can serve as practical alternative media for technology-integrated language instruction and support independent pronunciation practice in secondary school contexts. Highlights: Learners’ post-intervention scores increased compared with baseline performance. Statistical testing confirmed a meaningful difference after the treatment phase. Audio models with phonetic guidance enabled independent practice during reading tasks. Keywords: U-Dictionary; English Pronunciation; Narrative Story; Mobile-Assisted language Learning; EFL Students